2015
DOI: 10.1890/13-2257.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing biophysical controls on Gulf of Mexico hypoxia through probabilistic modeling

Abstract: A mechanistic model was developed to predict midsummer bottom-water dissolved oxygen (BWDO) concentration and hypoxic area on the Louisiana shelf of the northern Gulf of Mexico, USA (1985-2011). Because of its parsimonious formulation, the model possesses many of the benefits of simpler, more empirical models, in that it is computationally efficient and can rigorously account for uncertainty through Bayesian inference. At the same time, the model incorporates important biophysical processes such that its param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(95 citation statements)
references
References 59 publications
5
90
0
Order By: Relevance
“…We estimate that the probability that hypoxia would be <5,000 km 2 under an 80% load reduction is 87%. The 59% reduction is larger than the 45% reduction called for in the most recent Action Plan (17), but within the range of previous individual models (5,30,31,(33)(34)(35)(36). This percentage is also higher than recommendations made for other eutrophic systems.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…We estimate that the probability that hypoxia would be <5,000 km 2 under an 80% load reduction is 87%. The 59% reduction is larger than the 45% reduction called for in the most recent Action Plan (17), but within the range of previous individual models (5,30,31,(33)(34)(35)(36). This percentage is also higher than recommendations made for other eutrophic systems.…”
Section: Discussionmentioning
confidence: 48%
“…Previous studies suggested no apparent correlation between hypoxic area (or predictive errors) in 1 y and either N load or hypoxic extent in the previous year. Thus, including predictors representing carryover effects from the previous year did not substantially improve model fit (31,35,69). The loads used by each model show similar interannual patterns (Fig.…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations